LMNA-related dilated cardiomyopathy - Vaikhanskaya, Tatiyana (Oxford University Press, 2014)
A case of idiopathic dilated cardiomyopathy (DCM) that is likely to be associated with LMNA mutation Arg190Pro in a heterozygote is described. The features of DCM in the patient were conduction disorders, cardiac arrhythmias, progressive heart failure and minor musculoskeletal disturbances. We consider that the mutation Arg190Pro contributes to the formation of a weak nuclear lamina and diminishes muscle mechanical stability which is critical during cardiac contraction. The case report illustrates in detail the phenotypic manifestations of the novel LMNA mutation and difficulties in management related to it.